Protocolo para el entrenamiento del instrumentista en la planta de gas, Sardinata sur Ecopetrol, Tibú (2021)
The purpose of this undergraduate work is to design the protocol for instrumentalist training at the Sardinata sur Ecopetrol gas plant, located in the municipality of Tibú Norte de Santander. In the gas plant, the measurement and monitoring of variables that occur in industrial processes that are related to gas pumping are carried out, such as level, pressure, flow, temperature, among others. These signals are transmitted through a control loop which must be calibrated according to the established maintenance program. For this purpose, a series of knowledge in electronics, instrumentation, pneumatics, electricity, OSH standards and the environment is required by the plant instrumentalist who is in charge of this work. According to the above, a fairly rigorous training plan is needed that contains all the knowledge of the different processes, which is why the design of the training protocol for the floor instrumentalist is presented, made up of several modules that contain all the information specified from such that the trainee can be self-taught and develop their training in the same plant under the supervision of a suitable person to direct and evaluate the training.